Ergenlikte Kawasaki hastalığı - (:unkn) unknown (My University, 2013)
Kawasaki hastalığı, erken çocukluk döneminde görülen, koroner arter tutulumu nedeniyle hastalık ve ölüme yol açan bir vaskülittir. Büyük çocuk ve ergenlerde nadir görülmesi tanının gecikmesine neden olarak koroner arter tutulumu için bir risk etmeni oluşturabilir. Kliniğimizde ergen yaşta Kawasaki hastalığı tanısı koyduğumuz koroner arter genişlemesi ve akciğer tutulumu da gözlenen bir olgumuzu sunuyoruz.

Kawasaki disease is a vasculitis causing morbidity and mortality due to coronary artery involvement which is more frequent during infancy and early childhood. Since the disease is rare in older children and adolescents, the diagnosis may be delayed and the risk of coronary artery involvement may increase. We herein present a case of Kawasaki disease diagnosed in an adolescent patient, involving the coronary arteries and the lungs.
Kawasaki disease in adolescence
Keywords: Kalp ve Kalp Damar Sistemi; Pediatri; Periferik Damar Hastalıkları